Causal relationships between modifiable risk factors and polycystic ovary syndrome: a comprehensive Mendelian randomization study - Zhao, Yuheng; Pang, Jinglin; Fang, Xingyi; Yan, Zhaohua; Yang, Haili; Deng, Qinghua; Ma, Tianzhong; Lv, Mengqi; Li, Yingying; Tu, Ziying; Zou, Lin (Frontiers in Endocrinology, 2024)
Background: Various factors, such as lifestyle, environment, and iron metabolism, have been proposed as potential contributors to Polycystic Ovary Syndrome (PCOS) . However, a systematic assessment of modifiable risk factors and their causal effects on PCOS is lacking. This study aims to establish a comprehensive profile of modifiable factors for PCOS utilizing two-sample Mendelian Randomization (MR). Methods: Over 400 modifiable factors were analyzed with MR, including the Inverse Variance Weighted (IVW), Weighted Median, and MR-Egger. The reliability of our estimates underwent rigorous sensitivity analyses, encompassing Cochran's Q test, MR-Egger intercept analysis, leave-one-out analysis, and funnel plots. Results: Genetically predicted smoking per day, smoking initiation,body mass index, basal metabolic rate, waist-to-hip ratio, whole body fat mass,trunk fat mass,overall health rating, docosahexaenoic acid (DHA) (22:6n-3), monounsaturated fatty acids, other polyunsaturated fatty acids apart from 18:2, omega-3 fatty acids, ratio of bisallylic groups to double bonds, omega-9 and saturated fatty acids, total lipids in medium VLDL, phospholipids in medium VLDL, phospholipids in very large HDL, triglycerides in very large HDL, the genus Oscillibacter, the genus Alistipes, the genus Ruminiclostridium 9, the class Mollicutes, and the phylum Tenericutes, showed a significant effect on heightening genetic susceptibility of PCOS. In contrast, factors including fasting insulin interaction with body mass index, sex hormone-binding globulin, iron, ferritin, SDF1a, college or university degree,years of schooling, household income, the genus Enterorhabdus, the family Bifidobacteriaceae, the order Bifidobacteriales, the class Actinobacteria, and the phylum Actinobacteria were determined to reduce risk of PCOS.Conclusions: This study innovatively employs MR to assess causal relationships between 400 modifiable factors and the susceptibility of PCOS, offering novel insights into potential strategies for the management and treatment of PCOS.